2023
DOI: 10.3390/vaccines11040731
|View full text |Cite
|
Sign up to set email alerts
|

An Oral Galectin Inhibitor in COVID-19—A Phase II Randomized Controlled Trial

Abstract: Background: SARS-CoV-2 vaccines play an important role in reducing disease severity, hospitalization, and death, although they failed to prevent the transmission of SARS-CoV-2 variants. Therefore, an effective inhibitor of galectin-3 (Gal-3) could be used to treat and prevent the transmission of COVID-19. ProLectin-M (PL-M), a Gal-3 antagonist, was shown to interact with Gal-3 and thereby prevent cellular entry of SARS-CoV-2 in previous studies. Aim: The present study aimed to further evaluate the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This review proposed the idea of using Gal-3 antagonists given the structural similarity, which is remarkably studied to have benefits to clinical prognostication. Prolectin-M, a gal-3 antagonist, was studied for the treatment of SARS-CoV-2 infection (Galectin Antagonist Use in Mild Cases of SARS-CoV-2; pilot feasibility randomized, open label, controlled trial [109]). inhibitor, GB0139, when compared to standard treatment [86].…”
Section: Galectin Inhibitors In Pulmonary Fibrosis and Covid-19 Respi...mentioning
confidence: 99%
“…This review proposed the idea of using Gal-3 antagonists given the structural similarity, which is remarkably studied to have benefits to clinical prognostication. Prolectin-M, a gal-3 antagonist, was studied for the treatment of SARS-CoV-2 infection (Galectin Antagonist Use in Mild Cases of SARS-CoV-2; pilot feasibility randomized, open label, controlled trial [109]). inhibitor, GB0139, when compared to standard treatment [86].…”
Section: Galectin Inhibitors In Pulmonary Fibrosis and Covid-19 Respi...mentioning
confidence: 99%
“…Galectin-3 may play a role in sustaining HBV replication through stimulating the production of cytokines and chemokines via Cluster of Differentiation 98 (CD98) interactions with macrophages [23]. In the context of SARS-CoV-2, Gal-3 inhibition could potentially influence viral RNA synthesis [24].…”
Section: Galectin-3 In Viral Replicationmentioning
confidence: 99%
“…Small molecule inhibitors targeting Gal-3 have shown potential as antiviral agents in preclinical studies, reducing viral replication and alleviating virus-induced inflammation [24]. The Gal-3 inhibitor TD139 has demonstrated significant reductions in lung fibrosis and ß-catenin activation in animal models of pulmonary fibrosis and is now in phase IIb trials for the treatment of idiopathic pulmonary fibrosis and COVID-19 [109].…”
Section: Small Molecule Inhibitors Of Galectin-3mentioning
confidence: 99%
“…In the case of SARS-CoV-2, it has been shown that lectin receptors such as DC-SIGN, L-SIGN, CLEC4G and SIGLEC can bind to the glycans on the surface of the S protein and “hold” the virus in close proximity to cells, thereby facilitating more efficient infection [ 41 , 42 , 43 , 44 , 45 ]. There is also evidence that soluble lectin proteins—such as galectins—can bind to virions and bring them in close proximity to host cells, also facilitating infection [ 46 , 47 , 48 ]. This is particularly pertinent for the progression of COVID-19 since SARS-CoV-2 virions are transmitted via airborne routes and infection initiates in the proximal airways [ 42 , 49 ].…”
Section: Introductionmentioning
confidence: 99%